PAR-1 and PAR-2 Expression Is Enhanced in Inflamed Odontoblast Cells - Alvarez, M. M.P.; Moura, G. E.; Machado, M. F.M.; Viana, G. M.; de Souza Costa, C. A. [UNESP]; Tjäderhane, L.; Nader, H. B.; Tersariol, I. L.S.; Nascimento, F. D. (SAGE Publications, 2017)
Protease-activated receptors (PARs) are G protein–coupled receptors, which are activated by proteolytical cleavage of the amino-terminus and act as sensors for extracellular proteases. We hypothesized that PAR-1 and PAR-2 can be modulated by inflammatory stimulus in human dental pulp cells. PAR-1 and PAR-2 gene expression in human pulp tissue and MDPC-23 cells were analyzed by quantitative polymerase chain reaction. Monoclonal PAR-1 and PAR-2 antibodies were used to investigate the cellular expression of these receptors using Western blot, flow cytometry, and confocal microscopy in MDPC-23 cells. Immunofluorescence assays of human intact and carious teeth were performed to assess the presence of PAR-1 and PAR-2 in the dentin-pulp complex. The results show for the first time that human odontoblasts and MDPC-23 cells constitutively express PAR-1 and PAR-2. PAR-2 activation increased significantly the messenger RNA expression of matrix metalloproteinase (MMP)–2, MMP-9, MMP-13, and MMP-14 in MDPC-23 cells (P < 0.05), while the expression of these enzymes decreased significantly in the PAR-1 agonist group (P < 0.05). The high-performance liquid chromatography and matrix-assisted laser desorption/ionization–time-of-flight mass spectrometry analysis showed the presence of MMP-13 activity cleaving PAR-1 at specific, noncanonical site TLDPRS42↓F43LL in human dental pulp tissues. Also, we detected a presence of a trypsin-like activity cleaving PAR-2 at canonical site SKGR20↓S21LIGRL in pulp tissues. Confocal microscopy analysis of human dentin-pulp complex showed intense positive staining of PAR-1 and PAR-2 in the odontoblast processes in dentinal tubules of carious teeth compared to intact ones. The present results support the hypothesis of activation of the upregulated PAR-1 and PAR-2 by endogenous proteases abundant during the inflammatory response in dentin-pulp complex.
Keywords: caries; dentin-pulp complex; matrix metalloproteinases; odontoblasts; proteinase-activated receptor (PAR); proteolytic enzymes